Exam and assessment of contents of social sciences in 5th and 6th grade of elementary school. Capacities, concepts, and procedures - Cosme Jesús Gómez Carrasco; José Monteagudo Fernández; Ramón López Lacal (Revista Electrónica Interuniversitaria de Formación del Profesorado)
The objective of this essay is to analyze the exams of 5th and 6th grade of Elementary School about social sciences. In this paper we will analyze the contents of history and geography and the mental operations necessary to respond to the questions of the exams. This investigation has been realised on 69 exams and 745 questions picked up in five schools of the Region of Murcia. The study of these instruments of assessment has allowed us to establish different categories between the capacities, the contents and the format of examination.